Constructs for Safe-use of Natural Health Products Among Malaysian Consumers - Roziman, Nur Syamila Mohd; Din, Wardah Mustafa; Mahadi, Zurina; Islahudin, Farida; Said, Mazlina Md. (International Journal of Social Science Research, 2023)
Since the outbreak of Covid-19 in 2020, people have become more health-conscious and thus felt responsible for taking care of their own health for long-term well-being. The public is more aware to seek extra health measures with alternative therapies as awareness of sustainable lifestyles was promoted before the vaccine was introduced. The term “natural” brings a positive attitude towards the product since most consumers perceive natural as safe even though it does not necessarily mean safer or better. There are many reports on natural health products that are adulterated with harmful substances, and many still do not have data on their efficacy, hence it is pivotal that consumers know the safe-use elements of natural health products. It is important for consumers to know and have the right knowledge regarding the safety of natural health products to prevent any adverse effects in the future. The objective of this study is to identify the safe-use elements perceived by consumers for natural health products. A qualitative approach of Focus-Group Discussion (FGD) is employed to elucidate the safe-use elements, and thematic analysis is being done on the qualitative data to explore the objective. There are 11 safe-use elements of natural health products mentioned by consumers. However, there is only 1 safe use element that is in line with the current regulation in Malaysia. A complete guideline on the safe use of natural herbal products for consumers is pivotal to maintain their general health and well-being.